NASM ESSENTIALS OF PERSONAL FITNESS TRAINING - Sutton, Brian G. (Jones & Bartlett Learning, 2022)
"NASM Essentials of Personal Fitness Training, Seventh Edition, teaches the foundations of exercise science, fitness assessments, nutrition, and how to grow a personal training business. Since 1987, the National Academy of Sports Medicine (NASM) has been a global leader in providing evidence-based certification and specializations. This text continues to lead the way by providing the most comprehensive resource for aspiring personal trainers, health and fitness professionals and enthusiasts. Through NASM's proprietary Optimum Performance Training (OPT(TM)) model, this text teaches a systematic approach for designing exercise programs that can help anyone reach their fitness goals. This text is a recommended resource for the NASM Certified Personal Trainer (CPT) certification. The NASM-CPT certification is accredited by the National Commission for Certifying Agencies (NCCA)"--